INTEGRITAS, AMANAH, DAN PROFESIONALISME BERBASIS KARAKTER ISLAMI - Herlina Herlina; Haris Riadi; Annisa Hidayati (Jurnal Manajemen Pendidikan, 2026)
The increasingly complex nature of the workplace requires organizations not only to focus on productivity but also to strengthen moral and ethical values in the performance of their work. From an Islamic perspective, integrity, trustworthiness, and professionalism are important values that can serve as the foundation for character development and an ethical work culture. This study aims to analyze the concepts of integrity, trustworthiness, and professionalism from an Islamic perspective as well as examining its contribution to fostering a work culture that is honest, transparent, and accountable. This study employs a qualitative approach using the library research method, involving a review of books, scientific journals, research articles, and relevant academic sources. The data were analyzed using descriptive-qualitative and conceptual methods by identifying, comparing, and synthesizing various research findings. The research findings show that integrity (Siddiq) forms the basis of honesty, trustworthiness forms the foundation of responsibility, while professionalism (Itqan and ihsan) fosters optimal work quality. The implications of this research lie in reinforcing the understanding that the integration of these three values can foster an ethical work culture while also making work activities a form of social worship.